Hubungan Islam dan Negara dalam Pandangan Ahmad Syafii Maarif - Leni Marlena (Pascasarjana UIN Fatmawati Sukarno Bengkulu, 2022)
Abstract: The purpose of this study is to determine the concept of the state in Islam and the relationship between Islam and the state according to Ahmad Syafii Maarif. To uncover the problem in depth and thoroughly, the author uses this type of library research with qualitative descriptive methods that are useful to provide information, facts and data about the concept of the state in Islam and the relationship between Islam and the state according to Ahmad Syafii Maarif, then the data is described , analyzed and discussed to answer these problems. From the results of this study found that: first, the concept of a state in Islam according to Ahmad Syafii Maarif is closer to the shura system. A democratic state, which applies the principle of shura, is best suited for a country's system. This is because the system is closer to the political ideals of the Qur'an, which places humans in the same position in the decision-making process for the common good. Second, the relationship between Islam and the state according to Ahmad Syafii Maarif is a symbiotic relationship, which is a relationship that needs each other and is mutual. Religion (Islam) requires the state as a means to realize moral ideals or teachings that are in the Qur'an, while the state needs religion (Islam) as a moral guide for all life of the state and society.Keywords: Islam, state, shura, democracy. Abstrak: Tujuan penelitian ini adalah untuk mengetahui konsep negara dalam Islam serta hubungan Islam dan negara menurut Ahmad Syafii Maarif. Untuk mengungkap persoalan tersebut secara mendalam dan menyeluruh, penulis menggunakan jenis penelitian pustaka (library research) dengan metode deskriptif kualitatif yang bermanfaat untuk memberikan informasi, fakta serta data mengenai konsep negara dalam Islam dan hubungan Islam dan negara menurut Ahmad Syafii Maarif, kemudian data tersebut diuraikan, dianalisis dan dibahas untuk menjawab permasalahan tersebut. Dari hasil penelitian ini ditemukan bahwa: pertama, Konsep negara dalam Islam menurut Ahmad Syafii Maarif lebih dekat kepada sistem syura. Negara yang berbentuk demokratis, yang menjalankan prinsip syura paling cocok untuk sistem sebuah negara. Hal ini dikarenakan sistem tersebut lebih dekat kepada cita-cita politik Al-Qur’an, yang menempatkan manusia pada posisi sama dalam proses pengambilan keputusan untuk kepentingan bersama. Kedua, Hubungan Islam dan negara menurut Ahmad Syafii Maarif adalah hubungan yang simbiotik, yaitu suatu hubungan yang saling membutuhkan satu sama lainnya dan bersifat timbal balik. Agama (Islam) membutuhkan negara sebagai sarana untuk mewujudkan cita-cita moral atau ajaran-ajarannya yang ada dalam Al-Qur’an, sedangkan negara membutuhkan agama (Islam) sebagai petunjuk moral bagi semua kehidupan bernegara dan bermasyarakat.Kata Kunci: Islam, negara, syura, demokrasi.